ANALISIS SEMIOTIKA PADA LIRIK LAGU “UNTUK KITA RENUNGKAN” KARYA EBIET G. ADE - Ulina, Trinity Dew; Syamsiah, Khoirunnisa Nur; Adwam, Urfiyani (STKIP PGRI SUMENEP, 2024)
This study examines the meaning in the lyrics of the song